2017
DOI: 10.1177/0266666917712337
|View full text |Cite
|
Sign up to set email alerts
|

Challenges faced by libraries in a democratic South Africa

Abstract: Community libraries are crucial for people to have access to information to satisfy their multiple needs. As custodians of information and knowledge in diverse spheres, they play a role in the socioeconomic development of nations. This article attempts to investigate challenges faced by libraries in three different settings in post-apartheid South Africa. The study adopted a qualitative research design. The users, librarians and a wellplaced official of the relevant department were interviewed. Convenience sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Today, a community information service is not only delivered to the people through printed books, but also through increased access to computers and the internet. Therefore, public and community libraries have a substantial role to play in providing access to technology-enhanced services, as well as in improving information and communication technology literacies of library users (Mojapelo 2017). Hart (2010: 83) noted that "providing internet connectivity to the developing world will help them realise goals for health, education, employment and poverty reduction".…”
Section: Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Today, a community information service is not only delivered to the people through printed books, but also through increased access to computers and the internet. Therefore, public and community libraries have a substantial role to play in providing access to technology-enhanced services, as well as in improving information and communication technology literacies of library users (Mojapelo 2017). Hart (2010: 83) noted that "providing internet connectivity to the developing world will help them realise goals for health, education, employment and poverty reduction".…”
Section: Prospectsmentioning
confidence: 99%
“…Therefore, despite the conditional grant by the DSAC, public and community libraries still face budget-related challenges (Mnkeni-Saurombe 2010, Mojapelo 2017. Due to lack of funding, other key success factors such as space, resources, electricity, internet connectivity, equipment and security are also affected.…”
Section: Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…All public libraries in South Africa fall under the Department of Sports, Arts and Culture. However, it has been noted that, even in post-apartheid South Africa, community libraries are faced with an avalanche of daunting challenges against their mandate to provide library resources for all (Mojapelo 2018). Besides enormous challenges with funding and staffing, Mojapelo (2018) indicated that community libraries, particularly in disadvantaged rural communities, are not getting sufficient support from local governments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, it has been noted that, even in post-apartheid South Africa, community libraries are faced with an avalanche of daunting challenges against their mandate to provide library resources for all (Mojapelo 2018). Besides enormous challenges with funding and staffing, Mojapelo (2018) indicated that community libraries, particularly in disadvantaged rural communities, are not getting sufficient support from local governments. This problem of public libraries not meeting the information needs of their users is not only encountered in South Africa, but in other countries as well.…”
Section: Literature Reviewmentioning
confidence: 99%